Digital Subtraction Angiography of Anterior Cerebral Artery Complex in Indian Population at Two Tertiary Super-Specialty Hospitals (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Cerebral circulation has different variations in blood supply. Anterior cerebral artery is an important terminal branch of internal carotid artery. It forms the anterior component of circle of Willis along with the anterior communicating artery. The knowledge of anatomical variations in anterior cerebral artery is of considerable help to clinicians.Objective: The purpose of the study is to find out common anatomical variations of anterior cerebral artery complex by digital subtraction angiography in Indian population.Methodology: This descriptive cross-sectional study was conducted in the Neurointervention department of Max Super-specialty Hospital, New Delhi and Neo Multi-specialty Hospital, Noida, India during July 2016 to December 2016 for a period of six (06) months. Patients admitted in the Neurointervention department for digital subtraction angiography (DSA) were included in this study. Sampling technique was purposive. The angiogram machine was SIEMENS Artis Zee system and framing rate was 4f/sec. Morphology and variations of the anterior cerebral arteries and the anterior communicating artery were studied in 75 patients undergone cerebral DSA.Results: Variations were found in 48% (n=36). Variations of the segments in relation with size, course, communications and terminations of the anterior cerebral artery (ACA) were noted. These were divided into different groups like hypoplasia, aplasia, duplication and fenestrations. Hypoplasia/Aplasia of proximal anterior cerebral artery (A1) was 13.3% in right side and 5.3% in left side. Anterior communicating artery (AComA) was found absent in 10.7% and fenestration in 12%. Callosomarginal artery was found absent in 1.3% in right side and 5.3% in left side. In right callosomarginal artery 6.8% had abnormal origin and 4.2% abnormal in left side. Pericallosal artery was present 100% on both sides.Conclusion: Variations of anterior cerebral artery complex anatomy is found common in Indian population. Among them hypoplasia/aplasia is most commonJournal of National Institute of Neurosciences Bangladesh, 2018;4(1): 12-17